APLIKASI REGRESI ORDINAL PADA FAKTOR YANG BERPENGARUH TERHADAP AKTIFITAS ENZIM CHOLINESTERASE DARAH (Studi di Dusun Binangun Desa Bumiaji Kecamatan Bumiaji Kota Batu) - Diky Novariyanto; Arief Wibowo (The Indonesian Journal of Public Health, 2019)
The case of pesticide contamination in Batu City in 2017 wasrelatively high, with the percentage of 82.7%. The case of pesticide contamination could be detected by examining the cholinesterase enzyme activity in blood.The Bumiaji villagers (Batu City) mostly work as a pesticide spray farmers. The study aims to analyze the factors that affect cholinesterase enzyme’s activities on the blood of the farmers who spray pesticide. The study was observational with cross-sectional design and used ordinal regression method. The research sampleswere 81 farmers selected through accidental sampling method. The independent variables of this study were the use of Personal Protective Equipment (PPE) and farmers’work duration. The dependent variable of this study was the cholinesterase enzyme’s activities in the farmers’ blood. The results of the study were that most farmers experienced cholinesterase enzyme activity changes, misused PPE (80.2%), and worked for less than 8 hours each day (92.6%). Based on the ordinal regression analysis, the variables which affected to the cholinesterase enzyme activity of the farmers’ blood was the use of PPE with a p-value of 0.00 <α (0.05). Based on the regression model, the farmers who properly used PPE had 0.12 higher chance to avoid the change of cholinesterase enzyme activity in the blood. It is necessary to held a disseminationabout the use of personal protective equipment to the farmers, as a preventive effort by the district health office, local village office, and the management of farmer groups in Binangun sub-village, Bumiaji Village, Bumiaji Subdistrict, Batu City.